Solid waste management in local hospitals of the north of Valle del Cauca, Colombia - Patricia Torres L; Carlos A. Madera P; Luis F. Marmolejo R (Universidad de Antioquia, 2010)
Health-care institutions must offer adequate conditions for both employers and users in order to maintain, improve or recover their health status; inadequate health-care solid waste (h s w) management is an obstacle to achieve this goal. Objective:to estimate the quantity and composition of h s w in ten healthcare public institutions located in ten municipalities in northern Valle del Cauca region (Colombia). Methodology: quantity and composition of h s w was estimated through two 24 hours sampling rounds. Results: the proportion of hazardous healthcare solid waste (h h s w) was usually equal to or higher than 25% and it also surpassed the mean average values reported by organizations like World Health Organization; bio-sanitary waste was the category with major proportion in the h h s w fraction. Discussion: the values obtained in order to determine indicators as kg/bed-day and kg/patient-day were in a lower or equal range of those values reported by different institutional or scientific sources. Considering the health-care services offered in the evaluated institutions, the kg/patient-day indicator is considered more representative than the kg/bed-day.